2014
DOI: 10.1007/s40265-014-0228-2
|View full text |Cite
|
Sign up to set email alerts
|

Albiglutide: First Global Approval

Abstract: Albiglutide (Eperzan® [EU]; Tanzeum™ [US]), a glucagon-like peptide 1 receptor agonist, has been developed by GlaxoSmithKline for the treatment of type 2 diabetes mellitus (T2DM). Albiglutide has received its first global approval in this indication in the EU, for use in combination with other antihyperglycaemic agents, including basal insulin, when these drugs and diet and exercise do not provide adequate glycaemic control, and as monotherapy in patients unable to take metformin due to contraindications or in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(19 citation statements)
references
References 11 publications
0
18
0
1
Order By: Relevance
“…It has a half-life of~8 days in humans and is currently in a phase II clinical trial for the treatment of type II diabetes mellitus (109). The recently FDA-approved drug, albiglutide, is a DPPIV-resistant GLP-1 dimer fused to human albumin and has a half-life of 6-7 days, which enables weekly dosing for the treatment of type 2 diabetics (110,111).…”
Section: And Fusion To Long-live Plasma Proteinsmentioning
confidence: 99%
“…It has a half-life of~8 days in humans and is currently in a phase II clinical trial for the treatment of type II diabetes mellitus (109). The recently FDA-approved drug, albiglutide, is a DPPIV-resistant GLP-1 dimer fused to human albumin and has a half-life of 6-7 days, which enables weekly dosing for the treatment of type 2 diabetics (110,111).…”
Section: And Fusion To Long-live Plasma Proteinsmentioning
confidence: 99%
“…Furthermore, while many albumin-fusions are still in clinical trials, the first (Tanzeum ® ) was approved by FDA in 2014, which is a fusion of glucagon-like peptide-1 (GLP-1) to the Nterminal end. This drugs is used for treatment of type II diabetes and has a half-life of 5 days in humans [241,242]. A list of therapeutic molecules that has been genetically fused to albumin is shown in Table 3.…”
Section: Genetic Fusion To Albuminmentioning
confidence: 99%
“…14,15 Several of these, including exenatide and liraglutide, are currently available for treating type 2 diabetes. 16,17,18 Exenatide and liraglutide have both been shown to improve markers of endothelial function in vitro and in animal models. [19][20][21] Additional studies with liraglutide confirmed that this effect is dependent on the GLP-1 receptor.…”
Section: Introductionmentioning
confidence: 99%